(untitled) (Biological Sciences - PJSIR, 2003)
The creep properties (creep rate, creep modulus, creep compliance and tensile creep) of natural rubber loaded separately with local clay, limestone, silica-sand and charcoal have been examined as a function of filler loading. filler particle size, stress level and temperature. Results reveal that creep rate increases with increasing loading, stress level and temperature. The clay loaded composites show lower creep rate and energy to resist deformation tha n for composites loaded with limestone, silica sand and charcoal. Clay therefore shows a clear advantage over limestone, silica-sand and charcoal in creep deformation resistance when used as fillers in natural rubber.